Dual-targeted transferrin and AS1411 aptamer conjugated micelles for improved therapeutic efficacy and imaging of brain cancer - Chauhan M.; Singh R.P.; Sonali; Yadav B.; Shekhar S.; Kumar L.; Mehata A.K.; Jhawat V.; Dutt R.; Garg V.; Kailashiya V.; Muthu M.S. (My University, 2025)
Brain tumors represent an aggressive form of cancer, posing significant challenges in achieving complete remission. Development of advanced therapies is crucial for improving clinical outcomes in cancer patients. This study aimed to create a novel treatment approach using dual-targeted transferrin (TF) and AS1411 conjugated micelles, designed to enhance therapeutic effectiveness of docetaxel (DTX) and facilitate gadolinium (Gd) based imaging in brain cancer. Micelles were prepared using a slightly modified solvent-casting method, and the dual-targeting ligands were attached to the micelle's surface through a physical adsorption process. Average particle size of micelles ranged from 117.49 ± 3.90–170.38 ± 3.39 nm, with a low polydispersity index. Zeta potential ranged from − 1.5 ± 0.02 to − 18.7 ± 0.04 mV. Encapsulation efficiency of DTX in micelles varied from 92.64 ± 4.22–79.77 ± 4.13 %. Simultaneously, encapsulation of Gd in micelles was found to be 48.27 ± 3.18–58.52 ± 3.17, respectively. In-vitro drug release studies showed a biphasic sustained release profile, with DTX and Gd release continuing up to 72 h with their t50 % at 4.95, 11.29, and 24.14 h for GDTP, GDTP-TF and GDTP-TF-AS1411 micelles, respectively. Cytotoxicity effect of GDTP-TF-AS1411 micelles has shown significant improvement (P < 0.001) and reduced IC50 value up to 0.19 ± 0.14 μg/ml compared to Taxotere® (2.73 ± 0.73 μg/ml). Theranostic study revealed higher accumulation of GDTP-TF and GDTP-TF-AS1411 micelles free GD treated animal brains. The AUC of GDTP-TF-AS1411 micelles exhibited 23.79 ± 17.82 μg.h/ml higher than Taxotere® (14.14 ± 10.59 μg.h/ml). These findings direct enhanced effectiveness in brain cancer therapy leading to improved therapeutics in brain cancer patients. The combined targeted ligands and therapeutic agents strategy can direct advancement in brain cancer therapy and offer improved therapy for patients. © 2023 Elsevier B.V.